COMPARISON OF THE CHARACTERISTICS OF BOILED-SMOKED SAUSAGES WITH THE REQUIREMENTS OF EXISTING STANDARDS FOR THESE PRODUCTS AND COMPLIANCE WITH THE LAWS OF UKRAINE ON THE PROTECTION OF CONSUMER RIGHTS - Приліпко, Тетяна; Руснак, Леся; Букалова, Наталья (Modern engineering and innovative technologies, 2025)
The results of the research of the characteristics of the "Serveda" of the highest grade with the requirements of the current standards for these products and compliance with the laws of Ukraine on the protection of consumer rights. Analyzing the range of